Association of Serum Carotenoids and Retinoids with Intraprostatic Inflammation in Men without Prostate Cancer or Clinical Indication for Biopsy in the Placebo Arm of the Prostate Cancer Prevention Trial. (2nd January 2022) - Chadid, Susan; Song, Xiaoling; Schenk, Jeannette M.; Gurel, Bora; Lucia, M. Scott; Thompson, Ian M.; Neuhouser, Marian L.; Goodman, Phyllis J.; Parnes, Howard L.; Lippman, Scott M.; Nelson, William G.; De Marzo, Angelo M.; et al.
Abstract: Non-supplemental carotenoids and retinol may potentiate antioxidant and anti-inflammatory mechanisms. Chronic intraprostatic inflammation is linked to prostate carcinogenesis. We investigated the association of circulating carotenoids and retinol with intraprostatic inflammation in benign tissue. We included 235 men from the Prostate Cancer Prevention Trial placebo arm who had a negative end-of-study biopsy, most (92.8%) done without clinical indication. α-carotene, β-carotene, β-cryptoxanthin, lycopene, and retinol were assessed by high-performance liquid chromatography using pooled year 1 and 4 serum. Presence and extent of intraprostatic inflammation in benign tissue was assessed in 3 (of 6–10) biopsy cores. Logistic (any core with inflammation vs none) and polytomous logistic (some or all cores with inflammation vs none) regression was used to estimate odds ratios (OR) and 95% confidence intervals (CI) of intraprostatic inflammation by concentration tertile adjusting for age, race, prostate cancer family history, and serum cholesterol. None of the carotenoids or retinol was associated with intraprostatic inflammation, except β-cryptoxanthin, which appeared to be positively associated with any core with inflammation [vs none, T2: OR (95% CI) = 2.67 (1.19, 5.99); T3: 1.80 (0.84, 3.82), P -trend = 0.12]. These findings suggest that common circulating carotenoids and retinol are not useful dietary intervention targets for preventing prostate cancer via modulating intraprostatic inflammation.